How to change the previous result ?
1 Ansicht (letzte 30 Tage)
Ältere Kommentare anzeigen
Yamina chbak
am 12 Jun. 2021
Beantwortet: Sulaymon Eshkabilov
am 13 Jun. 2021
Hi, I want to compute the solution :
for n=2,... where
. With the initial solution
.
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650955/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650960/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650965/image.png)
For example :
if n=2,
then ![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650975/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650970/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650975/image.png)
if n=3,
, it's possible to rewrite S as :
where S is the previous result has stored but have to replace
with
, then compute ![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/651000/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650980/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650985/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650990/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650995/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/651000/image.png)
if n=4,
, it's mean
where S is the previous result has to replace
with
and
with
.
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/651005/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/651010/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650990/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650995/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/650995/image.png)
![](https://www.mathworks.com/matlabcentral/answers/uploaded_files/651030/image.png)
and continue .....
Here what i did :
S = 0;
U1 = 5;
k = 0;
for n=2:10
% Compute the sum term
k = k+1;
b = sqrt(n-k+1)-sqrt(n-k);
S = S+b*U1;
% Compute the new solution
U = S+10;
% Overwrite the solution to change the result of the sum S : S = b*U;
% without use the index U(i)
U1 = U;
% but it's not correct
end
What I do ?
0 Kommentare
Akzeptierte Antwort
Sulaymon Eshkabilov
am 13 Jun. 2021
There was an err inside the loop. Here is the corrected complete and simplified code:
S = 0;
U = 5;
for n=2:10
b = sqrt(n)-sqrt(n-1);
S = S+b*U;
U = S+10;
end
fprintf('Final values: S = %f and U = %f \n', [S, U])
0 Kommentare
Weitere Antworten (0)
Siehe auch
Kategorien
Mehr zu Loops and Conditional Statements finden Sie in Help Center und File Exchange
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!